The engineering design process - Ertas, Atila; Jones, Jesse C. (New York : John Wiley & Sons, Inc., 1993)
The Engineering Design Process has been written to fulfill the need for a textbook appropriate for use in the capsone senior design project cource. It is intended to foste a thorough understanding of the engineering design process, from the recognition of a need and teh definition of design objectives through product certification and manufacture of the prototype.
The engineering design process -- Managing design projects -- Modeling and simulation -- Design analyses for material selection -- Engineering economics -- Optimization in design -- Statistical descisions -- Design for reliaility -- Safety and environmental protection -- Engineering ethics -- Communications in engineering
Includes index.
Keywords: ENGINEERING DESIGN